Antiseptics... Renaissance in the therapy of vulvovaginal infections or new perspectives and expectations? - Yu.E. Dobrokhotova; Semioshina O. E. (РМЖ. Мать и дитя, 2018)
Antiseptics… Renaissance in the therapy of vulvovaginal infections or new perspectives and expectations? Dobrokhotova Yu.E., Semioshina O. E. Pirogov Russian National Research Medical University, Moscow Vulvovaginal infections are one of the most common obstetric and gynecological diseases and one of the main causes of applying to the gynecologist. In recent years, the prevalence of mixed infections has become a characteristic feature. However, the preventive administration of antibiotics as the first line therapy is erroneous and unacceptable, given the rapidly decreasing effectiveness of antibacterial drugs and constantly increasing resistance of microorganisms. A good alternative to the initial (and sometimes – the only) stage of treatment of mixed vulvovaginal infections may be the use of antiseptic drugs, in particular, based on iodine, which has a number of significant advantages (pluripotent effect, good penetrating power, including biofilm penetrating, low acquired resistance formation, good local tolerance, etc.). To neutralize the strong oxidative effect of the iodine molecule on healthy cells and body tissues, a complex compound of halogen and an inert synthetic polymer of polyvinylpyrrolidone (Betadine) was created. Vaginal suppositories Betadine can be used as an initial step in the therapy of vaginal infections even before the results of bacteriological cultures test are obtained. Key words: vaginal biocenosis, disbiosis, vulvovaginal infections, vaginitis, antiseptics, povidone – iodine, alternative to antibacterial drugs, antibiotic resistance, combination drugs, pluripotent effect. For citation: Dobrokhotova Yu.E., Semioshina O.E. Antiseptics… Renaissance in the therapy of vulvovaginal infections or new perspectives and expectations ? // RMJ. 2018. № 2(I). P. 39–42.